Ready, set-- WAIT! : what animals do before a hurricane - Zelch, Patti R. (Sylvan Dell Publishing, 2010)
A hurricane is forming over the ocean. Humans get ready by boarding up windows and gathering food and supplies. But what do wild animals do before and during hurricanes? Based on scientific research and noted observations, this book answers that question about a variety of different animals. Includes "For Creative Minds" educational section.